World university rankings and the future of higher education - Downing, Kevin; Ganotice, Fraide A., 1975- (Advances in educational marketing, administration, and leadership, 2017)
"This book is a pivotal reference source for the latest scholarly research on the implementation of a ranking system for higher education institutions, providing a thorough overview of the impacts of these rankings on educational quality"--Resumé vydavatele